A Circum-Pacific Perspective on the Origin of Stemmed Points in North America. (2nd January 2020) - Pratt, Jordan; Goebel, Ted; Graf, Kelly; Izuho, Masami
ABSTRACT: The Western Stemmed and Paleocoastal technocomplexes are prevalent in western North America. A working hypothesis states they are associated with the late-Pleistocene human migration into the Americas and derive from an antecedent located along the North Pacific Rim. Here, we review their records to create a techno-typological baseline, which we then compare to early archaeological records from the North Pacific Rim, Beringia, Siberia, and Russian Far East. Our results indicate stemmed points and related socket hafting were an important component of Upper Paleolithic technology across northeast Asia since at least the last glacial maximum. An associated diagnostic bifacial reduction strategy is present by the early part of the late glacial, and continues in younger technocomplexes. Future research should continue to focus on analyses of the chronological and technological relationships between different technocomplexes to uncover their evolutionary origins.